THE STAGES OF LANGUAGE ACQUISITION IN CHILDREN: A COMPARATIVE STUDY OF THEORIES - Purba, Elan Nuroctavia; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
Language acquisition in children is a remarkable and complex process that unfolds naturally as they grow, forming the foundation of their ability to communicate and interact with the world. From the first sounds a baby makes to the construction of full sentences, children follow a predictable pattern of language development. Understanding how this process occurs has long been a central focus of research in the field of psycholinguistics, leading to the creation of several influential theories. Each theory offers a different explanation for how children acquire language. Some, like the behaviorist theory, emphasize the role of environmental factors such as imitation and reinforcement. Others, such as the nativist theory, propose that children are born with an inherent ability to learn language, guided by an innate grammar. Cognitive and interactionist theories highlight the importance of cognitive development and social interaction in shaping language skills. This mini research aims to explore and compare the major theories of language acquisition by examining how each explains the various stages of development in children. By investigating these perspectives, this study seeks to provide a clearer understanding of how children learn language and what factors contribute most significantly to their linguistic growth.